2014
DOI: 10.2337/db14-0213
|View full text |Cite
|
Sign up to set email alerts
|

Nardilysin-Dependent Proteolysis of Cell-Associated VTCN1 (B7-H4) Marks Type 1 Diabetes Development

Abstract: T-cell responses directed against insulin-secreting pancreatic β-cells are the key events highlighting type 1 diabetes (T1D). Therefore, a defective control of T-cell activation is thought to underlie T1D development. Recent studies implicated a B7-like negative costimulatory protein, V-set domain-containing T-cell activation inhibitor-1 (VTCN1), as a molecule capable of inhibiting T-cell activation and, potentially, an important constituent in experimental models of T1D. Here, we unravel a general deficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 39 publications
5
34
0
Order By: Relevance
“…1C). These findings echoed our recent report describing a highly similar phenotype of progressive VTCN1 protein loss (coupled with compensatory VTCN1 mRNA up-regulation) in MФs and DCs from T1D-succeptible subjects, which occurred due to proteolysis of cell-associated VTCN1 by the metalloproteinase NRD1 (22). Hence, we compared dynamics of islet NRD1 expression and observed a significant age-dependent elevation of NRD1 mRNA in NOD, but not B6 g7 islets (Fig.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…1C). These findings echoed our recent report describing a highly similar phenotype of progressive VTCN1 protein loss (coupled with compensatory VTCN1 mRNA up-regulation) in MФs and DCs from T1D-succeptible subjects, which occurred due to proteolysis of cell-associated VTCN1 by the metalloproteinase NRD1 (22). Hence, we compared dynamics of islet NRD1 expression and observed a significant age-dependent elevation of NRD1 mRNA in NOD, but not B6 g7 islets (Fig.…”
Section: Resultssupporting
confidence: 88%
“…RT-qPCR analysis using primers specific for VTCN1 , NRD1 , PCSK1, or PCSK2 was performed as previously described (22). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results showed a trend of higher sB7-H4 in diabetic children, though not statistically significant. This data agreed with a more recent study, which confirmed that sB7-H4 were elevated in newly-onset T1D patients [62] . Previous characterization of the B7-H4 gene using human multiple cDNA panels demonstrated that there are two major versions of B7-H4 transcripts from the pancreas tissue: A full-length (2.0 kb) transcript which is shared with other organs, and a shorter (1.2 kb) transcript version which is specific for pancreas [23,24] .…”
Section: T1dsupporting
confidence: 83%